2016
DOI: 10.1055/s-0036-1584822
|View full text |Cite
|
Sign up to set email alerts
|

Common Pediatric Skin Lesions: A Comprehensive Review of the Current Literature

Abstract: The timely diagnosis and treatment of dermatologic disease in the pediatric population can be challenging. A basic, yet comprehensive knowledge of common lesions is essential for a successful practice in plastic surgery. In this article, the authors describe vascular, cystic, and pigmented cutaneous lesions that are commonly encountered in the pediatric population. Epidemiology, pathogenesis, clinical course, and management options are discussed for each.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…As a result, early childhood treatment is now widely acknowledged. 7,8 Based on the assumption that surgery would reduce the risk of complications and had significant effects on relaxing local symptoms and improving the appearance, resection and reconstructive surgery remained the primary treatment for decades. 9,10 There are numerous surgical techniques available, the most basic and often used including serial excision, 11 tissue expansion, 12 and skin grafting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, early childhood treatment is now widely acknowledged. 7,8 Based on the assumption that surgery would reduce the risk of complications and had significant effects on relaxing local symptoms and improving the appearance, resection and reconstructive surgery remained the primary treatment for decades. 9,10 There are numerous surgical techniques available, the most basic and often used including serial excision, 11 tissue expansion, 12 and skin grafting.…”
Section: Introductionmentioning
confidence: 99%
“…Excision of these lesions early on may lessen the incidence of malignant melanoma and the suffering associated with it 2 . As a result, early childhood treatment is now widely acknowledged 7,8 …”
Section: Introductionmentioning
confidence: 99%
“…The quantitative risk of malignant transformation to melanoma is unknown. Some studies have reported that there could be a 1% chance for small and medium CMN and 5% for larger CMN, with about half the risk in the first few years of life [2]. Approximately 50% of melanoma develops by age two and 80% by age seven; thus, surgery at an early age is recommended [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported that there could be a 1% chance for small and medium CMN and 5% for larger CMN, with about half the risk in the first few years of life [2]. Approximately 50% of melanoma develops by age two and 80% by age seven; thus, surgery at an early age is recommended [2][3][4]. Removal of a large or giant facial CMN requires a suitable donor site and often multiple procedures to achieve the best esthetic outcome.…”
Section: Introductionmentioning
confidence: 99%